The Impact of Hyperglycemia on VEGF Secretion in Retinal Endothelial Cells - Caprnda, Martin; Kubatka, Peter; Saxena, Sandeep; Valaskova, Jela; Stefanickova, Jana; Kobyliak, Nazarii; Zulli, Anthony; Kruzliak, Peter (Folia medica, 2017)
BACKGROUND: Diabetic retinopathy is a serious sight-threatening complication which is manifested by excessive angiogenesis in diabetic patients. AIM: We hypothesize that cultured Rhesus monkey retinal endothelial cells (RhRECs) respond to high glucose with a change in cell proliferation and vascular endothelial growth factor (VEGF) secretion. MATERIALS AND METHODS: In our study, 20 000 cells per well were treated without glucose or with 5.5 mM, 18.5 mM and 30 mM glucose for 24 hours. Viable cells were counted using trypan blue dye exclusion method. VEGF concentrations were measured in cell media by ELISA method. RESULTS: The number of viable cells incubated with 5.5 mM glucose increased significantly by 53.7% after 24 hours. In comparison, the number of viable cells decreased by 2.8% at 18.5 mM of glucose and by 20.4% at 30 mM of glucose after 24 hours of incubation. In contrast to this effect of glucose on the number of viable cells, a significant increase in VEGF levels (pg/mL) in the cell media with a glucose concentration of 0 mM compared to 5.5 mM of glucose was found. VEGF secretion in cell medium with 18.5 and 30 mM of glucose increased non-significantly in comparison with euglycemic levels. CONCLUSION: Our results show that viability of retinal endothelial cells and VEGF release are highly responsive to changes in glucose concentration. Such glucose-induced changes in retinal endothelial cells may negatively impact the integrity of the microvasculature in the diabetic retina leading to angiogenesis and microaneursym.
Keywords: Glucose; viabilita buněk; hyperglykemie; Male; Endothelial Cells; endoteliální buňky; Cell Proliferation; Haplorhini; Diabetic Retinopathy; Cell Survival; Retina; glukosa; mužské pohlaví; glucose; referenční hodnoty; ELISA; diabetická retinopatie; Hyperglycemia; diabetic retinopathy; VEGF; kultivované buňky; Reference Values; Enzyme-Linked Immunosorbent Assay; Animals; lidé; ženské pohlaví; Humans; zvířata; Sensitivity and Specificity; senzitivita a specificita; proliferace buněk; Haplorrhini; vaskulární endoteliální růstový faktor A; Cells, Cultured; Vascular Endothelial Growth Factor A; retina; retinal endothelial cell; Female